Los conflictos familiares y su influencia en el comportamiento de un niño de 11 años - Banderas Sánchez, José Antonio (2020)
The case study with which you are going to work, is a child who has behavior and learning problems. The knowledge that will be shared in this work contributes to professional growth since psychological techniques are detected in practice through the application of the research methods provided by this science, the information obtained in this case study can not be generalize because it is not working with a sample of a population. Conflicts influence family members and children are usually those who are most vulnerable to these circumstances and they will be affected and their effect is to develop aggressive behaviors, it is the way the family male expresses. All the problems that the family has causes them to generate behavior in both parents and children, which is why the emotions that are generated in the home as a result of the behaviors of each individual in the family system. The influence that family conflict has on behavior will be identified through the descriptive investigation of which applying the respective psychological techniques will affect the corresponding information.